Henry and Mudge and the tumbling trip : the twenty-seventh book of their adventures - Rylant, Cynthia (Rylant, Cynthia. Henry and Mudge books., 2005)
Henry, his parents, and his dog Mudge take a vacation out West, where they enjoy tumbleweeds, desert animals, souvenirs, and the wide open spaces.